Probiotic bacteria-released extracellular vesicles enhance macrophage phagocytosis in polymicrobial sepsis by activating the FPR1/2 pathway - Ruiyao Zhu; Yu Zhang; Xiaohong Wang; Benjamin D. Liu; Debabrata Chowdhury; Zhixin Li; Mingliang Pan; Tianqing Peng; Jing Chen; Wei Huang; Liying Zhan; Guo-Chang Fan (BMC, 2024)
Abstract Background Sepsis-induced organ failure and high mortality are largely ascribed to the failure of bacterial clearance from the infected tissues. Recently, probiotic bacteria-released extracellular vesicles (BEVs) have been implicated as critical mediators of intercellular communication which are widely involved in the regulation of the inflammatory response. However, their functional role in macrophage phagocytosis during sepsis has never been explored. Methods BEVs were collected from three different strains of probiotics including Lactiplantibacillus plantarum WCFS1 (LP WCFS1), Lactobacillus rhamnosus Gorbach-Goldin (LGG), and Escherichia coli Nissle 1917 (EcN), or from LGG cultured under three pH conditions (pH5-acid, pH6.5-standard, pH8-akaline) through differential centrifugation, filtration, and ultracentrifugation of their culture supernatants. In vitro phagocytosis was measured in Raw264.7 cells and bone marrow-derived macrophages using pHrodo red E. coli BioParticles. The in vivo therapeutic effects of BEVs were tested using a feces-injection-in-peritoneum (FIP) model of polymicrobial sepsis. Results LGG-derived EVs (BEVLGG) were the best among these three probiotics BEVs in stimulating macrophages to take up bacteria. Furthermore, BEVLGG collected from pH8 culture condition (BEVpH8) exhibited the strongest capacity of phagocytosis, compared with BEVpH5 and BEVpH6.5. Treatment of septic mice with BEVpH8 significantly prolonged animal survival; increased bacterial clearance from the blood, peritoneal lavage fluid, and multiple organs; and decreased serum levels of pro-inflammatory cytokines/chemokines, as well as reduced multiple organ injuries, in comparison with control-treated septic mice. Mechanistically, RNA-seq and bioinformatic analysis identified that the FPR1/2 signaling was remarkably activated, along with its downstream pathways (PI3K-Akt-MARCO and NADPH-ROS) in BEVpH8-treated macrophages, compared with control cells. Accordingly, pre-addition of Boc2, a specific antagonist of FPR1/FPR2, to macrophages significantly attenuated BEVpH8-mediated phagocytosis, compared to controls. Conclusions This study demonstrates that LGG-derived BEVs may have therapeutic effects against sepsis-induced organ injury and mortality through enhancing FPR1/2-mediated macrophage phagocytosis.